Evaluasi Kinerja Portofolio Dengan Indeks Treynor Pada Portofolio Optimal Dan Portofolio Acak Di Bursa Efek Indonesia - Efflan, Jourdan Septiansyah (Arthavidya Jurnal Ilmiah Ekonomi, 2019)
This study aims to determine the composition of the optimal portfolio using a single index model, determine the composition of the random portfolio using naive diversification, then evaluate the performance of the portfolio formed using the Treynor index. This study uses monthly stock closing price data listed on the Indonesia Stock Exchange during the research period of August 2016 to July 2018. The optimal portfolio formed using a single index model consists of 40 shares, while a random portfolio consists of 10 shares. The results of the Treynor portfolio performance evaluation show that the optimal portfolio formed by the single index model method has better portfolio performance than the random portfolio.